A French network for prevention and reduction of reproductive risk in couples and pregnant women. (13th November 2019) - Sunyach, C; Perrin, J; Bretelle, F; Paris, C; Garlantezec, R; Belacel, M; Pairon, J-C; Sentilhes, L; Delva, F; Brochard, P
Abstract: Background: Since 2013, several international (ASRM, FIGO, ACOG) and French (ANSES) learned societies and the French National Health and Environment Plan (2015-2019) urged to take into account exposures to environmental reprotoxic substances during standard care of infertile couples and pregnant women. However perinatal health professionals hardly incorporate this recommendation into practice. Objectives: To create a network of platforms to addressing the environmental aspects that can impact the pregnancy chances of infertile couples after ART and pregnancy outcomes. We asked regional health authorities in France to provide funding for multidisciplinary hospital structures, in conjunction with clinical-biological reproductive health and gynecology-obstetric centers. Expertise, as well as information leaflets and risk detection tools have been shared. Results: Platforms of counselling and prevention have been set up in the University Hospitals of Bordeaux, Marseille, Rennes, Créteil and Paris Fernand-Widal. Infertile couples and pregnant women, referred by reproductive physicians, benefit from personalized management of their domestic/professional reprotoxic exposures by addictology/tobacco, dietetics, occupational health and environmental pathology professionals. The network organizes an annual scientific day and a common database of exposure is being set up. Conclusions: The PREVENIR (PREVENTION - ENVIRONMENT - Reproduction) network of platforms allows perinatal health professionals to refer their patients in order to optimize their chance of pregnancy through personalized and multidisciplinary care. The lifestyle changes initiated through this approach will also improve pregnancy outcomes and child health. Key messages: A French network for the prevention and reduction of reproductive risk in infertile couples and pregnant women: the PREVENIR platforms (PREVENTION - ENVIRONMENT - Reproduction) is being established. Perinatal health professionals of multidisciplinary platforms engage into preventive actions to limit the exposure to environmental hazards during preconception and pregnancy.